(untitled) (Biological Sciences - PJSIR, 2004)
50 50 Toxicity of Clerodendrum inerme (dumdum leaves extract) and cyhalothrin (Pyrethroid) was tested against adult beetles of Rhizopertha dominica. Filter paper impregnation method was adopted for the determination of LC dose. LC dose of C. inerme and cyhalothrin was found to be 1460 µg/cm2 and 0.00063 µg/cm2, respectively. Biochemical estimation revealed that both the products inhibited the acid phosphatase and cholinesterase activity to some extent.